On the application of constant electrode potential simulation techniques in atomistic modelling of electric double layers. Issue 10 (3rd July 2017) - Vatamanu, Jenel; Bedrov, Dmitry; Borodin, Oleg
Abstract: This paper presents a brief overview of molecular simulation techniques utilised to simulate the electrode/electrolyte interfaces. We introduce a simple scheme to perform classical molecular dynamics (MD) simulations at constant electrode potential and show that the original constant potential method that employs Gaussian distributed charges can be modified by adding an energy term proportional to the electrode charge squared while keeping other electrostatic interactions similar to those of point charges. Therefore the scheme shown here can be straightforwardly implemented in most MD simulation codes as it requires no modification of the standard energy and force evaluation routines. The impact of the exclusion of Gaussian cross terms of the electrode–electrode and electrode–electrolyte electrostatic interactions is extensively quantified and compared against the original method allowing us to examine the sensitivity of electric double layer (EDL) simulations to the choice of Gaussian width. This scheme provides accurate predictions of EDL structure, electrode charge density and differential capacitance.